Multiple Mononeuropathy: Keys in its identification to avoid wrong diagnosis - Ricaurte-Fajardo, Andrés (2019)
Mononeuropathy Multiplex (MM) is one of the classic peripheral neuropathies along with polyneuropathies. MM is defined as the involvement of two or more nerves in more than one limb of simultaneous or sequential appearance. Its presentation can be similar to polyneuropathies. Therefore, it is imperative to complete an in-depth medical history, with an emphasis on relevant background and neurological examination. Diagnosis of MM should not be confused with other polyneuropathies, given that the treatment is manly based on the control of the underlying disease, that is generating the symptoms. Wrongful diagnosis can lead to treatments with unnecessary cost which, is unfavourable for the patient. Consequently, an organized process of identification of the disease should be completed.